Robotic sphincter saving rectal cancer surgery: A learning curve analysis. Issue 4 (9th June 2020) - Aghayeva, Afag; Baca, Bilgi
Abstract: Background: Longer operation time is one of the major obstacles in front of the proposed benefits of robotic rectal surgery. We intended to evaluate the learning process for robotic surgery in sphincter saving rectal cancer surgery. Methods: The learning curve was evaluated using the cumulative sum (CUSUM) method. The variable evaluated for learning curve calculation was the operative time. Results: The learning curve was divided into two phases: initial 52 operations comprised phase 1 and the following 44 operations represented phase 2. Interphase comparisons showed that phase 2 patients had shorter operation times (323.3 ± 102.8 vs. 379.9 ± 108.7 min, p = 0.011), less blood loss (37.2 ± 51.0 vs. 87.7 ± 124.8 mL, p = 0.009), longer distal resection margins (4.5 ± 4.3 vs. 2.5 ± 1.7 cm, p = 0.008), and higher rates of grade 3 mesorectal completeness (p = 0.001). Conclusion: In this study, we saw that the cut‐off level in the learning curve of a laparoscopically experienced surgeon could be beyond the numbers reported in the literature.